Pengaruh Variasi Presentase HCL Terhadap Laju Korosi, Nilai Kekerasan dan Struktur Mikro Sambungan Las TIG Baja ST 60 - Irvan Nurfajri; Viktor Naubnome; Rizal Hanifi (Peneliti.net, 2022)
The purpose of this study was to determine the effect of variations in the percentage of HCL on the rate of corrosion. corrosion, to determine the effect of variations in current strength on the hardness value and microstructure of ST 60 steel. This study used an experimental method including the preparation of tools and materials, specimen making, welding process and corrosion rate testing, micro hardness vicker hardness. Then the highest corrosion rate value was obtained. of 3.6873996123 mm/year. The highest hardness value is at a current of 140 A in the weld metal area with a hardness value of 242.3 HV and the lowest hardness value is at a current of 120 A in the base metal area of ​​169.5 HV. The conclusion in this study is that the higher the current, the lower the corrosion rate will be inversely proportional to the hardness value, where the higher the amperage, the harder the hardness value